Surah Yasin: Kajian perbandingan antara Qira’at Nafi dan Qira’at Asim riwayat Hafs / Murshidi Abd Hamid - Murshidi , Abd Hamid (2010)
Knowledge on Qira’at appeared when the al-Qur’an was revealed but many among us do not have this particular knowledge. In reality, this knowledge is closely associated with penalties and this reflects the significance of Qira’at. The main intention to introduce this subject of Qira’at is to expose to the public the importance of Qira’at as a source of knowledge with authenticity in Islam in tandem with the al-Qur’an. The main focus in this study is a comparison between two Qira’at for surah Yasin. This study is intended to introduce Qira’at Nafi‘ and Hafs and to gather more details on the respective Qira’at. The writer has chosen surah Yasin as a sample since it is widely read by the believers and most mosques schedule the reading of this surah on Thursday evenings. The main data is obtained through a comparison of similarities and differences in reading between Imam Nafi‘ and Hafs. Beyond that, data is also obtained by listing the words in the surah Yasin which have been in dispute among the scholars. As a result of the detailed studies on Imam Nafi‘ and Hafs, their fore-fathers, relatives, descendents, date of birth and death besides their detail methodology of studies. Their methodology of studies are analysed beginning with the Usul and Farsh Huruf. Once both areas are well comprehended , the debates on those topics will be simply understood. In undertaking this study, various methods have been used, including reference to recognized books on this topic. Besides those, the writer has made reference to journals and academic studies which have been produced in order to complete this study. Not forgetting, interviews were held to identify the problems relating to the pronounciation of each word (kalimah). This study recommends to the relevant authority to ensure the inclusion of this knowledge on Qira’at in the national syllabus besides taking relevant actions to enhance the knowledge in facing the modern cyber knowledge. The main challenge in propagating this knowledge is how serious is the government to propagating this knowledge is how to serious is the government to popularize it to the whole nation. This study also recommends that knowledge on Qira’at to be made as a thrust subject to the national education system.